How to lose friends & alienate people - Young, Toby, 1963- (Abacus, 2008)
In 1995, high-flying British journalist Toby Young left London for New York to become a contributing editor at Vanity Fair. Other Brits had taken Manhattan - Alistair Cooke, Tina Brown, Anna Wintour - so why couldn't he? Surely, it would only be a matter of time before the Big Apple was in the palm of his hand. But things did not go according to plan. Within the space of two years he was fired from Vanity Fair, banned from the most fashionable bar in the city and couldn't get a date for love or money. Even the local AA group wanted nothing to do with him. How To Lose Friends & Alienate People is Toby Young's hilarious account of the five years he spent steadily working his way down the New York food chain, from glossy magazine editor to crash-test dummy for interactive sex toys. But it's not just a collection of self-deprecating anecdotes. It's also a seditious attack on the culture of celebrity from inside the belly of the beast. Not since Bonfire of the Vanities has the New York A-list been so mercilessly lampooned - and it all really happened!